On the asymmetric effects of exchange‐rate volatility on trade flows: Evidence from Korea‐U.S. commodity trade. (29th December 2020) - Bahmani‐Oskooee, Mohsen; Baek, Jungho
Abstract: Previous studies that investigated the impact of exchange rate volatility on Korean trade flows assumed that the effects are symmetric. When we change this assumption and investigate the asymmetric effects of the real won‐dollar volatility on 61 U.S. exporting industries to Korea and on 49 U.S. importing industries from Korea, we discover relatively more significant and asymmetric effects. Indeed, we find short‐run asymmetric effects in 37 U.S. exporting industries that last into significant long‐run asymmetric effects in 29 of them. We also find short‐run asymmetric effects on imports of 24 industries that last into significant long‐run asymmetric effects in 33 out of 49 industries.